INTRAHEPATIC CHOLESTASIS OF PREGNANCY: ADVERSE FETOMATERNAL OUTCOME - Dr Tania Singh; Dr M. Rasheed; Dr Nagaraja N; Dr Charu Jain; Dr Shahla Yazdani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Intrahepatic Cholestasis of Pregnancy (IHCP) has been observed with increased incidence of fetal distress, meconium, preterm labour, intra uterine death, postpartum hemorrhage and increased surgical interferences. So, the present study is designed with an aim to see the trends of fetomaternal outcome among cases of IHCP as well as to find the incidence of IHCP among study population. Material and Methods: In our study out of 954 deliveries conducted, 48 patients were diagnosed with IHCP. These patients were studied to see the impact of IHCP on fetomaternal outcome. Results: During the study period (1July 2022 -31Aug 2023), there were 954 deliveries, of which 48 (5.03%) were diagnosed with IHCP without any other co-morbidities. The mean age of these women was 27.23 ± 3.78 years in cases. Among these 43.8% were Primiparous and 56.3% were multiparous. 39 (81.3%) were in age group 20-30 years. The mean period of gestation was found to be (37.25+0.911) week and (2.9+1.98) days. the occurrence of PPH was higher among subjects with IHCP (8.3%) when compared to the subjects without IHCP (4.5%)